2010
DOI: 10.1515/jpem.2010.075
|View full text |Cite
|
Sign up to set email alerts
|

Cognition, Emotions and Quality of Life in Lithuanian Girls with Turner Syndrome after Growth Hormone Therapy Discontinuation

Abstract: Objective: to examine cognitive functions, emotional state and quality of life of patients with Turner syndrome (TS) after growth hormone therapy discontinuation. Patients and Methods: Anthropometric measurements, cognitive functioning, emotional state and quality of life of eighteen Lithuanian patients with TS were compared to that of age-and sex-matched controls. Height and weight of girls with TS were significantly lower than in the controls, though differences in body mass index were not significant. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 33 publications
0
22
1
3
Order By: Relevance
“…Our data showed grades of anxiety and depression scores in TS patients higher than the previous reports (Catinari et al, 2006;McCauley et al, 2011;Kilic et al, 2005;Lasaite et al, 2010;Cardoso et al, 2004); this could be explained by the small sample size in our study and the lack of facilities in our developing country which could detect and diagnose TS patients early with the lack of early interventions of any psychological issues in TS patients.…”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…Our data showed grades of anxiety and depression scores in TS patients higher than the previous reports (Catinari et al, 2006;McCauley et al, 2011;Kilic et al, 2005;Lasaite et al, 2010;Cardoso et al, 2004); this could be explained by the small sample size in our study and the lack of facilities in our developing country which could detect and diagnose TS patients early with the lack of early interventions of any psychological issues in TS patients.…”
Section: Discussioncontrasting
confidence: 85%
“…Many studies using parental evaluations and selfreport suggested psychiatric problems in girls and adolescents with TS, in the form of immaturity, diminished social relationships, poor self-concept, depression and social anxiety compared to age-matched controls (Saad et al, 2014;Catinari et al, 2006;McCauley et al, 2001;Kilic et al, 2005;Lasaite et al, 2010;Cardoso et al, 2004). These studies deeply investigated the psychopathological comorbidity in TS patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations